Industrial Weed Control with Plainview, Esplanade, and Method Application Timings - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this trial was to compare Plainview, Esplanade, and Method at three applications for season-long weed control in noncropland. Glyphosate alone provided no residual weed control. Plainview (indaziflam/aminocyclopyrachlor/imazapyr) at 64 oz/a applied in the early or late fall controlled kochia similarly to Krovar (bromacil/ diuron) late in the season. Either rate of Plainview, as well as the tank mixture of Esplanade (aminocyclopyrachlor) plus Method (indaziflam), provided complete woollyleaf bursage control regardless of application timing. No treatment of Krovar controlled woollyleaf bursage more than 60%.
Keywords: Total vegetation management; industrial weed control; woollyleaf bursage